(untitled) (Nóema, 2015)
This article aims to examine Giovanni Papini’s Pragmatism (undoubtedly the most noticeable and unusual within Italian pragmatists), by referring it particularly to William James’ thought; more specifically, it aims to enlighten both the agreeable cooperation and the mutual influence and admiration between Papini and James. In order to do this, in this paper the steps of the development of Papini’s Pragmatist theory will be retraced, by pointing out both its bond with Jamesian speculation (without forgetting its Bergsonian feature) and its originality and theoretical relevance, able to assert itself also beyond the Italian borders.